Perinatal outcome of pregnancies with previous stillbirth: a prospective case control study in tertiary care center - Lede, Snehal; Parpillewar Tadas , Moushmi (International Journal of Research in Medical Sciences, 2023)
Background: Aim was to examine the association between stillbirth in first pregnancy and adverse perinatal outcome in second pregnancy. To determine risk factors causing recurrent stillbirth. Methods: This study was conducted at Government Medical College, and hospital, Nagpur. It was prospective case control study with cases as patients who had stillbirth in previous pregnancy and control as patient who had live birth in previous pregnancy. Results: There was 10 fold increased risk of recurrent stillbirth in cases compared to control. Preeclampsia was major risk factor followed by placental abruption; congenital anomaly and preterm labour were responsible for recurrent stillbirth. Conclusions: History of stillbirth in first pregnancy is associated with adverse perinatal outcome in form of recurrent stillbirth, increased NICU admission and neonatal death. Risk reduction by elimination of risk factor, proper antenatal surveillance and close monitoring during labour helps to reduce recurrent stillbirth.